Constitutional Public Order and its Applications under The Constitution of The Republic of Iraq for The year 2005 - Talib, Musadaq (Journal of Legal Sciences, 2023)
This research deals with the idea of ​​a constitutional public order, determining its nature, and its applications in light of the Constitution of the Republic of Iraq for the year 2005, by reviewing the relevant constitutional and legal texts, and comparing them with the principles followed by the Federal Supreme Court on the one hand, as well as comparing the behavior of the Iraqi constitutional legislator with some Comparative trends relevant to this topic, especially in Egypt and France, in order to try to draw a road map related to this idea in Iraqi legislation and jurisdiction.The importance of the research is the scarcity and lack of in-depth studies by constitutional jurists in Iraq despite their abundance in the writings of comparative jurisprudence, as well as the practical importance that is embodied in the knowledge of the position of the Iraqi constitutional judiciary represented by the Federal Supreme Court of the idea of ​​a constitutional public order, and the evaluation of these applications in the light of constitutional and legal texts .The research aims at defining the frameworks and boundaries between the constitutional public order and the public system in other branches of law, as well as evaluating the constitutional formulation that the 2005 Constitution of the Republic of Iraq has applied in defining the idea of ​​a constitutional public order under the prevailing political, economic and social conditions, without losing sight of On evaluating the practical reality of applying the idea of ​​a constitutional public order in the decisions of the Federal Supreme Court.Therefore, the question that the broadcast aims to explain is the extent to which the constitutional public order relates to many changing ideas in the jurisprudence of constitutional law. the most important of which are: in the idea of ​​including constitutional rules, the idea of ​​public order, and the prevailing legal idea, and then defining the boundaries between them.